Poterie, ethnicité et Laurentie iroquoienne - Chapdelaine, Claude (Recherches amérindiennes au Québec, 1991)
Keywords: Autochtones; Iroquoiens; Poterie

The Westmount "Stone-lined Grave" Race (An Archaeological Note) - Lighthall, W. D. (Mémoires et comptes rendus de la Société royale du Canada, 1922)
Keywords: Autochtones; Iroquoiens

Comments on the Archaeology of the Dawson Site - Macneish, Richard S. (Cartier's Hochelaga and the Dawson Site, 1972)
Keywords: Archéologie; Hochelaga; Iroquoiens

Contact Material from the Dawson Site - Kidd, Kenneth E. (Cartier's Hochelaga and the Dawson Site, 1972)
Keywords: Autochtones; Hochelaga; Iroquoiens

Le peuple d'Hochelaga - Beaugrand-Champagne, Aristide (Les Cahiers des Dix, 1937)
Keywords: Autochtones; Hochelaga; Iroquoiens

1542-1642 - Beaugrand-Champagne, Aristide (Les Cahiers des Dix, 1942)
Keywords: Autochtones; Hochelaga; Iroquoiens

Dawson Site Physical Anthropology - Anderson, James E. (Cartier's Hochelaga and the Dawson Site, 1972)
Keywords: Autochtones; Hochelaga; Iroquoiens

New Hochelagan Finds in 1933 - Lighthall, W. D. (Mémoires et comptes rendus de la Société royale du Canada, 1934)
Keywords: Autochtones; Hochelaga; Iroquoiens

The False Plan of Hochelaga - Lighthall, W. D. (Mémoires et comptes rendus de la Société royale du Canada, 1932)
Keywords: Autochtones; Hochelaga; Iroquoiens

Hochelaga and "The Hill of Hochelaga" - Lighthall, W. D. (Mémoires et comptes rendus de la Société royale du Canada, 1924)
Keywords: Autochtones; Hochelaga; Iroquoiens

Criteria for Identifying the Locations of Historic Indian Sites: a Case Study from Montreal - Trigger, Bruce Graham (Ethnohistory, 1969)
Keywords: Autochtones; Hochelaga; Iroquoiens

Montréal avant Maisonneuve - Lanctot, Gustave (La revue de l'Université Laval, 1957)
Keywords: Autochtones; Hochelaga; Iroquoiens

"La terra de Hochelaga" ou le plan de Ramusio de 1556 - Larouche, Pierre (Cap-aux-Diamants, 1994)
Keywords: Autochtones; Hochelaga; Iroquoiens

Les origines de Montréal - Beaugrand-Champagne, Aristide (Les Cahiers des Dix, 1948)
Keywords: Cartier, Jacques; Hochelaga; Iroquoiens

Le chemin de Jacques Cartier vers la bourgade d'Hochelaga - Achard, Eugène (E. Achard, 1969)
Keywords: Cartier, Jacques; Hochelaga; Iroquoiens

Natives and Newcomers: Canada's "Heroic Age" reconsidered - Trigger, Bruce Graham (McGill-Queen's University Press, 1994)
Plusieurs réimpressions
Keywords: Autochtones; Français; Iroquoiens; Iroquois

Cartier's Hochelaga and the Dawson Site - Trigger, Bruce Graham (Iroquois Culture, History and Prehistory. Proceedings of the 1965 Conference on Iroquois Research,, 1967)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

La découverte de Montréal, en 1535, par Jacques Cartier - Perrault, Claude (Loisirs Saint-Édouard, 1984)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

Archeological Comparison of Dawson Site with Other Iroquoian Sites in Eastern Ontario - Pendergast, James F. (Cartier's Hochelaga and the Dawson Site, 1972)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

Hochelaga: History and Ethnohistory - Trigger, Bruce G. (Cartier's Hochelaga and the Dawson Site, 1972)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

Cartier's Hochelaga and the Dawson Site - Pendergast, James F.; Trigger, Bruce G. (McGill-Queen's University Press, 1972)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

An Analysis of the Dawson Site Archaeological Material - Pendergast, James F. (Cartier's Hochelaga and the Dawson Site, 1972)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

Jacques Cartier va à Hochelaga - Malchelosse, Gérard (Les Cahiers des Dix, 1956)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

Le chemin et l'emplacement de la Bourgade d'Hochelaga - Beaugrand-Champagne, Aristide (Les Cahiers des Dix, 1947)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

La vie des indiens d'Hochelaga d'après les relations de Jacques Cartier - Verlhac, André (Annales de la faculté des lettres et sciences humaines, Université de Dakar, 1982)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

Le Chemin d'Hochelaga - Beaugrand-Champagne, Aristide (Mémoires et comptes rendus de la Société royale du Canada, 1923)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

La découverte de Montréal par Jacques Cartier - Perrault, Claude (Revue d'histoire de l'Amérique française, 1966)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

Cartier at Montreal - Burpee, Lawrence J. (Canadian Geographical Journal, 1946)
Keywords: Autochtones; Cartier, Jacques; Hochelaga; Iroquoiens

Les sépultures amérindiennes du Mont-Royal - Larocque, Robert (Recherches amérindiennes au Québec, 1990)
Keywords: Autochtones; Cimetières; Iroquoiens; Mont Royal

Le faux plan de la bourgade d'Hochelaga - Massicotte, E.-Z. (Bulletin des recherches historiques, 1935)
Keywords: Autochtones; Cartes et plans; Cartier, Jacques; Hochelaga; Iroquoiens